Investigating a Process of Accelerating Macroscopic Objects in an Eddy-Current Inductance Coil Magnetic Field - Andrzej HORODEŃSKI; Cezary POCHRYBNIAK; Kamil NAMYŚLAK (Problemy Mechatroniki)
The subject of this paper is an analysis of the process of applying kinetic energy to a projectile made of non-magnetic electrically conductive material and located inside an induction coil live with alternating current. An experimental verification was carried out of the analytical conclusions that were pertinent to the design and technology of an inductance coil gun, which is a ranged weapon type.